THE POTENTIAL OF FRANGIPANI FLOWER EXTRACT (Plumeria alba L.) AS AN ANTIBACTERIAL: A LITERATURE REVIEW - Hana Yuniestica Sinaga; Made Krisna Adi Jaya (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2022)
Background: Bacteria develop naturally in the human body to aid in protecting the individual. Antibiotic resistance is quickly increasing and is becoming a global health concern. In this situation, the risk of synthetic antibiotic resistance against bacterial infections makes it critical to find alternative medications that are safe, easy to obtain, and better than synthetic antibiotic alternatives. The frangipani plant is one of the medicinal plants used in traditional medicine as an antibacterial. The frangipani plant possesses antibacterial properties comparable to broadspectrum medicines against uro-gastro pathogens. Objective: The purpose of this study was to determine the activity of the frangipani flower as an antibacterial. Methods: studying literature from various databases, websites, national journals, and relevant international journals to identify frangipani flowers with antibacterial activity. Results: Results showed that frangipani flowers have antibacterial activity against gram-positive and gram-negative bacteria because frangipani flowers contain various antibacterial chemical components, such as terpenoids, saponins, phenols, flavonoids, tannins, and essential oils. Conclusion: Frangipani flowers have the potential to an antibacterial against gram-positive and gram-negative bacteria. Keywords: Frangipani flower; Antibacterial; Bacteria